2020
DOI: 10.1002/cbf.3589
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights of NADPH oxidases and its pathological consequences

Abstract: Reactive oxygen species (ROS), formed by the partial reduction of oxygen, were for a long time considered to be a byproduct of cellular metabolism. Since, increase in cellular levels of ROS results in oxidative stress leading to damage of nucleic acids, proteins, and lipids resulting in numerous pathological conditions; ROS was considered a bane for aerobic species. Hence, the discovery of NADPH oxidases (NOX), an enzyme family that specifically generates ROS as its prime product came as a surprise to redox bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 187 publications
(169 reference statements)
0
21
1
Order By: Relevance
“…For Nrf-2 to act as a transcription factor, it must be liberated from Kelch-like ECH-associated protein 1, a negative regulator of Nrf2, in the cytoplasm and phosphorylated before translocation to the nucleus 61 , 62 . Unlike HO-1, NOXs are key enzymes involved in the production of ROS as important regulators of redox homeostasis 63 , 64 . NOX consists of seven members, of which NOX2 acts as a major contributor of ROS generation during skeletal muscle contraction 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…For Nrf-2 to act as a transcription factor, it must be liberated from Kelch-like ECH-associated protein 1, a negative regulator of Nrf2, in the cytoplasm and phosphorylated before translocation to the nucleus 61 , 62 . Unlike HO-1, NOXs are key enzymes involved in the production of ROS as important regulators of redox homeostasis 63 , 64 . NOX consists of seven members, of which NOX2 acts as a major contributor of ROS generation during skeletal muscle contraction 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in many processes, including host defense, proliferation, regulation of gene expression, wound healing, and cell differentiation during embryogenesis. However, in case of uncontrolled increased activation or downregulation, pathological events occur [ 6 ], such as several degenerative and inflammatory diseases and the development and progression of cancer [ 7 ].…”
Section: Nox Structure and Functionmentioning
confidence: 99%
“…ROS derived from NOX can act by modulating various metabolic events, in particular gene expression, proliferation, cell migration, and angiogenesis [ 30 ]. In cancer cells, it has been demonstrated that oxidative stress leading to tumor initiation or progression may result from overproduction of ROS by members of NOX [ 31 ]. Among the different NOX isoforms, NOX 2 and 4 when deregulated have been associated with cancer; particularly, NOX4 overexpression has been shown in different types of cancers, such as renal and pancreatic cancers, and in glioblastoma and invasive breast cancers [ 31 ].…”
Section: Oxidative Stress In Cancer Metabolismmentioning
confidence: 99%
“…In cancer cells, it has been demonstrated that oxidative stress leading to tumor initiation or progression may result from overproduction of ROS by members of NOX [ 31 ]. Among the different NOX isoforms, NOX 2 and 4 when deregulated have been associated with cancer; particularly, NOX4 overexpression has been shown in different types of cancers, such as renal and pancreatic cancers, and in glioblastoma and invasive breast cancers [ 31 ]. However, conflicting evidence also suggests a role for NOX4 as a tumor suppressor: it has been shown that genetic deletion of NOX4 enhances cancerogen-induced formation of solid tumors [ 32 ]; moreover, NOX4 has been demonstrated to inhibit hepatocyte proliferation and liver cancer progression [ 33 ].…”
Section: Oxidative Stress In Cancer Metabolismmentioning
confidence: 99%